Haiti soberano - Dubois, Laurent (Afro-Ásia, 2021)
Resenha de: SALT, Karen. The Unfinished Revolution: Haiti, Black Sovereignty and Power in the Nineteenth-Century Atlantic World. Liverpool: Liverpool University Press, 2019. 240 p. GONZALEZ, Johnhenry. Maroon Nation: A History of Revolutionary Haiti. New Haven: Yale University Press, 2019. 320 p.